Estimasi Kepadatan Populasi Monyet Dihe (Macaca hecki) Di Desa Dulamayo Utara, Gorontalo - Terri Repi; Abdul Kadir Kadir N Giu; Ishak Korompot; Ramlan Pomolango (Jurnal Sains Ternak Tropis, 2026)
The dihe macaque (Macaca hecki) is one of the primates endemic to Sulawesi. This species is listed on the IUCN red list as vulnerable due to high pressure on its habitat and population. One of the distribution areas of M. hecki in Gorontalo Province is the Dulamayo Forest. However, until now, research on the population, habitat, and ecology of M. hecki has not been widely conducted. This study aims to determine the existence and estimate the population density of M. hecki in North Dulamayo village. The study was conducted for approximately 2 months (May–July 2025). The study used the strip transect sampling method for population data and vegetation analysis to determine the structure and composition of the habitat. The results of this study revealed that North Dulamayo Village is a distribution area of M. hecki, with the discovery of 31 individuals of M. hecki. Based on data analysis, the highest density was found on transect A, with a density of 19.2 individuals/Km2, while the lowest density was found on transect B, with a density of 7 individuals/Km2. Furthermore, based on the total survey area of 0.225 km2, the population density of M. hecki was 13.1 individuals/km2. The research results are expected to serve as a baseline for further research and policymaking on M. hecki conservation in Gorontalo Province, especially for population management, habitat and handling of human-wildlife conflicts. Monyet dihe (Macaca hecki) merupakan salah satu primata endemik Sulawesi. Spesies ini masuk daftar merah IUCN dengan kategori rentan akibat tingginya tekanan terhadap habitat dan populasi. Salah satu daerah sebaran M. hecki di Provinsi Gorontalo adalah Hutan Dulamayo. Namun sampai saat ini penelitian mengenai populasi, habitat dan ekologi M. hecki belum banyak dilakukan. Penelitian ini bertujuan untuk mengetahui eksistensi dan estimasi kepadatan populasi M. hecki di desa Dulamayo Utara. Penelitian dilakukan selama kurang lebih 2 bulan (Mei–Juli 2025). Penelitian menggunakan metode strip transect sampling method untuk data populasi dan analisis vegetasi untuk mengetahui stuktur dan komposisi habitat. Hasil penelitian mengungkapkan Desa Dulamayo Utara merupakan daerah sebaran M. hecki, dengan ditemukannya 31 individu M. hecki di jalur transek. Berdasarkan analisis data diperoleh kepadatan terbanyak terdapat pada jalur transek A, dengan kepadatan sebesar 19,2 ekor/Km2, sedangkan kepadatan terendah terdapat pada jalur transek B, dengan kepadatan sebesar 7 ekor/Km2. Selanjutnya, berdasarkan luas total area survey sebesar 0,225 Km2, diperoleh kepadatan populasi M. hecki sebesar 13,1 ekor/Km2. Hasil penelitian diharapkan dapat menjadi referensi awal bagi penelitian lanjutan dan pengambilan kebijakan konservasi M. hecki di Provinsi Gorontalo khususnya untuk manajemen populasi, habitat dan penanganan konflik manusia–satwa liar.